Penggunaan Metode Rough Set pada Tingkat Kecemasan (Anxietas) Mahasiswa dalam Menyusun Tugas Akhir - Nadilla Ayudia Pasa; Yani Maulita; I Gusti Prahmana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This study investigated college students' anxiety levels in completing their final projects, which is an important requirement for graduation. Anxiety is a common problem faced by students, which is often caused by the long and complicated process of preparing a final project. Using the Zung Self-Assessment Anxiety Scale (SAS/SRAS), this study aims to measure the level of anxiety and identify the main factors that contribute to it. The Rough Set Method, an efficient technique for analyzing uncertainty, was applied to identify patterns and relationships between factors influencing college students' anxiety. Data was collected through questionnaires from students who are currently completing their final projects. By applying the Rough Set Method, this research succeeded in identifying significant factors that influence anxiety levels, such as psychological, physical and positive responses. These findings provide valuable insight for educators and counselors to better understand and address college students' anxiety during the final years.